Knowledge Flow Model in Banking Industry - Sedigheh Mohammad Esmaeil; Fatemeh Hamidi (مدیریت راهبردی دانش سازمانی, 2021)
Objective: The present study intends to provide a model for knowledge flow in the banking industry by examining the existing models while evaluating the components involved in the knowledge flow. Method: This research is a descriptive-correlational research and is applied in terms of purpose. The statistical population of this study included the employees of the central offices of Bank Melli Iran, whose number is 2211 people. Using a Morgan table, a sample of 330 people was randomly selected from this population. Data collection tool is a 45-item researcher-made questionnaire in 8 dimensions, which was adjusted based on the Likert scale, the validity of this questionnaire was evaluated by two formal methods and factor analysis technique and its reliability was evaluated by Cronbach's alpha method, the results indicate the appropriate reliability and validity of the questionnaire. To analyze the research hypotheses, the method of structural equations using Smart PLS software has been used. Results: The components of knowledge acquisition, knowledge creation, knowledge storage, knowledge sharing, knowledge application, information technology infrastructure and flexible organizational structure Influence the flow of knowledge in the banking industry and the conceptual model of research is a good model for knowledge flow in the banking industry. Knowledge sharing with an impact factor of 0.379 has the greatest impact on knowledge flow status. Conclusion: The results show that the flow of knowledge in the banking industry is very necessary and this industry urgently needs to enter this field of study and operation. Knowledge management is also important in order to establish an effective flow of knowledge in the banking industry. Therefore, it is necessary for banks to first provide the necessary conditions for the effective flow of knowledge in the bank with proper knowledge management in the organization, and thus achieve better performance and profitability in this industry.